2014
DOI: 10.1093/scan/nsu148
|View full text |Cite
|
Sign up to set email alerts
|

Task-dependent and distinct roles of the temporoparietal junction and inferior frontal cortex in the control of imitation

Abstract: The control of neurological networks supporting social cognition is crucially important for social interaction. In particular, the control of imitation is directly linked to interaction quality, with impairments associated with disorders characterized by social difficulties. Previous work suggests inferior frontal cortex (IFC) and the temporoparietal junction (TPJ) are involved in controlling imitation, but the functional roles of these areas remain unclear. Here, transcranial direct current stimulation (tDCS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
86
3
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 82 publications
(103 citation statements)
references
References 67 publications
11
86
3
1
Order By: Relevance
“…Neurostimulation studies from our lab and others further showed a causal role of the rTPJ in self-other distinction (Bardi, Gheza, & Brass, 2017;Hogeveen et al, 2014;Santiesteban, Banissy, Catmur, & Bird, 2012;Sowden & Catmur, 2015). Research has shown reduced TPJ, and sometimes also mPFC activity in ASD during self-other distinction across several domains, including mentalizing (Eddy, 2016;Kennedy & Courchesne, 2008;Murdaugh, Nadendla, & Kana, 2014;Pfeifer et al, 2013;Spengler et al, 2010), adding to accumulating evidence that the TPJ is a core region implicated in ASD (Chien, Lin, Lai, Gau, & Tseng, 2015;Fishman, Keown, Lincoln, Pineda, & Müller, 2014;Kana, Uddin, Kenet, Chugani, & Müller, 2014).…”
Section: Introductionsupporting
confidence: 51%
“…Neurostimulation studies from our lab and others further showed a causal role of the rTPJ in self-other distinction (Bardi, Gheza, & Brass, 2017;Hogeveen et al, 2014;Santiesteban, Banissy, Catmur, & Bird, 2012;Sowden & Catmur, 2015). Research has shown reduced TPJ, and sometimes also mPFC activity in ASD during self-other distinction across several domains, including mentalizing (Eddy, 2016;Kennedy & Courchesne, 2008;Murdaugh, Nadendla, & Kana, 2014;Pfeifer et al, 2013;Spengler et al, 2010), adding to accumulating evidence that the TPJ is a core region implicated in ASD (Chien, Lin, Lai, Gau, & Tseng, 2015;Fishman, Keown, Lincoln, Pineda, & Müller, 2014;Kana, Uddin, Kenet, Chugani, & Müller, 2014).…”
Section: Introductionsupporting
confidence: 51%
“…Recent data on imitative compatibility (the tendency to perform an action faster when observing the same action than a different action; Heyes, 2011;Stürmer, Aschersleben, & Prinz, 2000), a behavioural effect that is thought to index mirror neuron function (Catmur, Walsh, & Heyes, 2009;Heiser, Iacoboni, Maeda, Marcus, & Mazziotta, 2003;Hogeveen et al, in press), supports the conclusion that mirror responses can occur with limited attention. Catmur (under review) used an imitative compatibility design to demonstrate that the mapping of an observed movement onto the motor program for that movement occurs under conditions of limited attention (however see Chong, Cunnington, Williams, & Mattingley, 2009, for an alternative finding); and Dainton, Catmur, and Marsh (in preparation) showed that attention affects spatial, but not imitative, compatibility.…”
Section: The Role Of Attention In Intention Understandingmentioning
confidence: 88%
“…Hogeveen et al (2015) indicated that anodal tDCS of the right TPJ improved the inhibition of imitation, but it did not facilitate imitation. Further, anodal tDCS of the right IFC improved both inhibition of imitation and imitation.…”
Section: Discussionmentioning
confidence: 99%